“Is Bay Area Regional Planner fun?” an analysis of game design in the face of urban planning - Samuelson, Stephen Timothy Mott (Kansas State University, 2020)
Play is an integral part of learning. Games address the human need to play, but with a structure of underlying mechanics designers can use them to create much more. Detailed simulations, abstract stories, and compelling drama are only the tip of what designers can create within games. Most importantly, games can use their rules to create dynamic experiences that respond to their player’s mistakes and successes in ways that other media cannot. This point is particularly compelling when considering how viable they are as a teaching tool. The Urban Planning field is constantly seeking new and creative ways to engage with community stakeholders and to solicit feedback, share information, and create lasting relationships. Games naturally fill these roles in childhood development, and continue into our adult lives, so we are left asking, “why shouldn’t we try using games to engage with stakeholders?” Because it’s hard. The ways in which games are used in community outreach must be as carefully designed as the games we play and communities we live in. We look to games that boldly dive into community outreach . Bay Area Regional Planner is a game that does so, being designed for a local community workshop in San Francisco. In order to understand the ways we can use games in the planning process, we must study Bay Area Regional Planner for both its successes and its failings. We pose the research question, “is Bay Area Regional Planner fun?” As I study the way the game unfolds, and unravel the workings of the designer’s intent, I ask not just if the game is fun but why and how. Ultimately, the answers both surprise and inspire us to see what could come next – and how the result could prove valuable to the Urban Planning field.
Keywords: Community engagement; Game design; Urban planning